Tüketim kooperatiflerinde kart sistemi ve muhasebeleştirilmesi - Alpaslan, Halil İbrahim (My University, 2004)
TÜKETİM KOOPERATİFLERİNDE KART SİSTEMİ ve MUHASEBELEŞTİRİLMESİ Bu çalışma Türkiye'nin en eski tüketim kooperatiflerinden olan Körfez Tükobirlik'in geliştirdiği indirim kartı ve muhasebe işlemlerini anlatmaktadır. Bir işletme çeşidi olan kooperatiflerin de küresel pazarlarda rekabet edebilmesi için yeniliklere ihtiyaçları vardır. MB Koop Kart Kocaeli bölgesinde Körfez Tukobirlik' e pozitif bir imaj kazandırmış başarılı bir uygulamadır. Türkiye'de kooperatifçilik hareketinin olumlu bir imaj kazanması açısından bu tür yardımcı araçlar çok önemli bir yer tutar Name and Surname: Halil İbrahim Alpaslan Field: Business Administration Programme: Cooperatives Supervisor: Associative Prf. Dr. Ayten Ersoy Degree of Awarded and Date: Master- July 2004- Key Words: Card System in Consumer Cooperatives and Accounting Records

CARD SYSTEM in CONSUMER COOPERATİVES and ACCOUNTING RECORDS This study is about the application of discount card system and its accounting records which is developped by Turkey's one of the oldest consumer cooperative called Korfez Tukobirlik. Cooperatives which are a kind of businesses, also need inovations in order to compete in the global markets. MB Koop Card is a successful innovation that creates a positive image for cooperatives in Kocaeli region. This contribution is very important for the movement in Turkey in terms of creating a positive image for cooperatives.
Keywords: Kooperatifler